Husband’s Support for Breastfeeding and Breastfeeding Efficacy of Nepalese Mothers - Nepali, Sajama; Shakya, Manodhara (Health Prospect, 2019)
Background: Continuing breastfeeding after three months of the postpartum period has been a challenge to mothers rather than their choice. The engagement of husbands in breastfeeding serves both as physical and mental support to their wives. This study aimed to assess the breastfeeding self-efficacy of mothers, identify their husbands’ support for breastfeeding and examine the association between breastfeeding self-efficacy of mothers and the husbands’ support for breastfeeding. Methods: This descriptive, cross sectional study recruited 110 mothers of infants, visiting Bungmati Health Post for immunization from July 2015 to November 2015. Mothers were interviewed face to face with semi structured questionnaire. Data entry and analysis was carried out using SPSS version 23. Descriptive analysis was performed on the socio-demographic characteristics, delivery characteristics, breastfeeding self-efficacy and husbands’ support scale. Bivariate analysis was used to examine the association between breastfeeding self-efficacy and husbands’ support scale and other outcomes. Results: Majority (94%) of the mothers reported to be confident on the breastfeeding self-efficacy, while 95 percent of their husbands were supportive towards breastfeeding. A significant association was seen between the breastfeeding self-efficacy and the husbands’ support scale (p<0.04). Mothers who received support from husbands were 10 times more likely to report confidence on breastfeeding than those who did not. Conclusions: The results suggested that husbands’ support increases the breastfeeding self-efficacy of mothers. Based on this finding, it is recommended that involvement of husband is crucial for encouraging mother to breastfeed child. Tweetable Abstract: Mothers who received support from their husbands were 10 times significantly more likely to breastfeed.